Concept analysis of family homeostasis. (11th August 2014) - Kim, Heejung; Rose, Karen M.
Abstract: Aim: To report a concept analysis of family homeostasis. Background: As family members are a majority of informal caregivers, negative consequences from caregiving duty create a vicious cycle in the family unit resulting in ongoing health crises and care challenges. Design: Concept analysis. Data Sources: Forty empirical studies published from 1956–2012 were selected by searching five electronic bibliographical databases and by a manual search conducted from 2012–2013. Search terms included 'family homeostasis', 'homeostasis in family', 'homeostatic care' and 'family equilibrium'. Clinical experiences in nursing practice were used for constructing cases and clinical implications. Methods: Walker and Avant's method guided this analysis. Results: Family homeostasis is defined as the capacity and mechanisms by which equilibrium is re‐established in the family after a change occurs. Five critical attributes are identified: (1) predetermined setpoint; (2) self‐appraised antecedents; (3) interdependence; (4) tendency to stability; and (5) feedback mechanisms. Antecedents include any type of causative change beyond the tolerable limit, while consequences encompass intermediate and long‐term outcomes as well as equilibrium itself. Conclusion: Family homeostasis provides a conceptual rationale of family caregiving. While care recipients remain the primary beneficiaries of healthcare provision, homeostatic mechanisms are required to support the family caregiver's valuable contribution in the caring process to enhance family well‐being. Further study should expand the definition and settings of family to reflect healthcare needs of diverse types of families and from the perspectives of different healthcare providers.